Perspective of Family and School: Environment Influences Technopreneur Behaviour of Vocational School Students - rahayu, imami; Hidayati, Lutfiyah; Ramadani, Ali Hasbi; Arizal, Heru; Nugroho, Yuli Sutoto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study investigates the influence of family and school environments on developing technopreneur behavior among vocational school students in East Java, Indonesia. The research aims to determine the extent to which these two factors contribute to fostering students' entrepreneurial skills in technology-driven businesses. Method: The research employs an ex post facto design, utilizing Structural Equation Modeling (SEM) to analyze data collected from 396 Fashion Design Skills program students. Data were gathered through tests and questionnaires, measuring students' technopreneur behavior, family environment, and school environment. Instrument validation was conducted using the Content Validity Ratio (CVR), item-total correlation, and Rasch model analysis. Results: The findings reveal that family and school environments significantly influence technopreneur behavior among vocational students. The family environment contributes 29.1%, while the school environment contributes 44.9% to developing technopreneur behavior. The combined influence of both factors explains 75.5% of the variation in students' technopreneur behavior. The study underscores the importance of supportive families and conducive school environments in fostering entrepreneurial mindsets among students. Novelty: This study provides empirical evidence on the combined role of family and school in shaping technopreneur behavior among vocational students, emphasizing the need for an integrated approach to entrepreneurship education. It highlights the importance of strategic curriculum design, teacher training, and family engagement in developing future technopreneurs.